AMPK/mTOR Signaling in Autophagy Regulation During Cisplatin-Induced Acute Kidney Injury - Wang, Ying; Liu, Zhiwen; Shu, Shaoqun; Cai, Juan; Tang, Chengyuan; Dong, Zheng (Frontiers in Physiology, 2020)
Autophagy is a conserved, multistep pathway that degrades and recycles dysfunctional organelles and macromolecules to maintain cellular homeostasis. Mammalian target of rapamycin (mTOR) and adenosine-monophosphate activated-protein kinase (AMPK) are major negative and positive regulators of autophagy, respectively. In cisplatin-induced acute kidney injury (AKI) or nephrotoxicity, autophagy is rapidly induced in renal tubular epithelial cells and acts as a cytoprotective mechanism for cell survival. Both mTOR and AMPK have been implicated in the regulation of autophagy in cisplatin-induced AKI. Targeting mTOR and/or AMPK may offer effective strategies for kidney protection during cisplatin-mediated chemotherapy.